Bone Marrow-Derived Stem Cells for Patients with Liver Cirrhosis: A Systematic Review and Meta-analysis - Ouyang, Shi; Ouyang, Lei; Li, Yuanq; Ye, Yaling; Ban, Li (Turkish Journal of Gastroenterology, 2021)
Background: To date, studies have shown inconsistent results of treatment with bone marrow-derived stem cells (BMDSC) for patientswith liver cirrhosis. This study aims to compare the efficacy and safety of BMDSC and standard therapy for liver cirrhosis.Methods: Articles from PubMed, Embase, and the Cochrane library were searched from inception to April 2018. The index included Modelfor End-stage Liver Disease (MELD), alanine aminotransferase (ALT), albumin, total bilirubin (TBIL), prothrombin time (PT), Child–Pughscore, and all-cause mortality.Results: A total of 9 studies with a total of 424 patients with liver cirrhosis were included in final meta-analysis. BMDSC therapy wasassociated with lower MELD within 3 months (P = .010), while it had no significant impact on MELD after 6 months (P = .074). There wereno differences between BMDSC and standard therapy for ALT within 3 months (P = .336) and after 6 months (P = .379). BMDSC did notaffect albumin level within 3 months (P = .196) and after 6 months (P = .840). BMDSC reduced the TBIL level within 3 months (P = .037)and was not associated with the TBIL level after 6 months (P = .914). There were no differences between BMDSC and standard therapyfor PT within 3 months (P = .167) and after 6 months (P = .484). The Child–Pugh scores within 3 months (P = .342) and after 6 months(P = .133) were not associated with BMDSC treatment for liver cirrhosis patients. Finally, the BMDSC was not associated with the risk ofall-cause mortality, as compared with standard therapy (P = .622).Conclusions: BMDSC treatment for patients with liver cirrhosis could improve short-term MELD and TBIL, but not the risk of mortality,as compared with standard therapy.